Chas. Ben. Darwin, Ordinances of the City of Burlington, with Head Notes and an Analytic Index Page 72-73 § 1-4 - (:unkn) unknown (General Publisher, 1847)
Prohibited any merchant, trader, or other person to retail or deliver gun powder during the night. Violators fined five dollars. Gun powder limited to twenty-five pounds and only in a "safe canister." Gun powder shall only be kept in dwellings approved by the Council. Violators fined one hundred dollars, with the powder confiscated with cost.
--
Keywords: GUN POWDER TRANSPORTATION